The Use of Web-Based Vocabulary Games to Improve Junior High School Students’ Vocabulary Mastery in Reading - Putri, Ananda Sadyva Aulia; Akhiriyah, Suvi (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2024)
Web-based game can be an alternative learning media for students to improve their vocabulary mastery in reading. Nevertheless, few studies look at how web-based games can be used as a teaching tool to help junior high school students improve their vocabulary, especially in context of reading. The main objective of this research is to know the differences between the improvement of vocabulary mastery of 7 grade students at a junior high school in Indonesia who use the web-based vocabulary game